Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 7 - Rational Functions - 7.2 Simplifying Rational Expressions - 7.2 Exercises: 19

Answer

$= \frac{(w-4)}{(w-3)}$

Work Step by Step

$\frac{w^{2}-16}{w^{2}+w-12}$ $= \frac{(w+4)(w-4)}{w^{2}+w-12}$ $= \frac{(w+4)(w-4)}{w^{2}+4w-3w-12}$ $= \frac{(w+4)(w-4)}{w(w+4)-3(w+4)}$ $= \frac{(w+4)(w-4)}{(w-3)(w+4)}$ $= \frac{(w-4)}{(w-3)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.